2015
DOI: 10.3402/gha.v8.27562
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary community service in medical school: a qualitative study on obstacles faced by student leaders and potential solutions

Abstract: PurposeIn medical school, students may participate in various community involvement projects (CIP), which serve disadvantaged communities. However, several obstacles may arise during these projects. The authors conducted a qualitative study with the primary aim of understanding the obstacles and corresponding potential solutions when medical students in Singapore participate in local CIP (LCIP) and overseas CIP (OCIP).DesignThe authors recruited medical students from Yong Loo Lin School of Medicine, National U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 25 publications
(35 reference statements)
3
15
0
Order By: Relevance
“…Common challenges faced by our students include comforting and communicating professionally, working independently, organizational issues, lack of resources and ethical issues. Similar to our ndings, studies have listed CSL challenges including language and cultural barriers or potential to harm the patient (34,40). A similar potential negative effect from the same study included creation of dependencies of local communities on the local clinic or at the level of government policies and health insurance (40).…”
Section: Challenges Of the Eventsupporting
confidence: 76%
See 2 more Smart Citations
“…Common challenges faced by our students include comforting and communicating professionally, working independently, organizational issues, lack of resources and ethical issues. Similar to our ndings, studies have listed CSL challenges including language and cultural barriers or potential to harm the patient (34,40). A similar potential negative effect from the same study included creation of dependencies of local communities on the local clinic or at the level of government policies and health insurance (40).…”
Section: Challenges Of the Eventsupporting
confidence: 76%
“…Similar to ours, another CSL model describes the effectiveness of such programs in developing the participants self-reported empathy, cultural competence, communication skills and openness towards peer teaching (3,31). Peer learning and support, which is another important nding of our study, has also been described by researchers as enhancing medical knowledge, procedural skills (32) along with the professional development of all students involved in such interactions (5,33,34). While developing a culture of community outreach, CSL programs similar to ours, have also shown improvement in student attitudes towards patients (35) and development of social accountability (36)(37)(38)(39).…”
Section: Overall Bene Tssupporting
confidence: 59%
See 1 more Smart Citation
“…Our findings are consistent with Clark et al (2015), which reported that the most common barriers for students working with community partners during the community service-learning program were scheduling difficulties and, in some cases, a lack of clarity of the students' roles. 1 The barriers specific to voluntary CEL activities included challenges in managing logistics and volunteers, which paralleled the phenomenological study conducted by Loh et al (2015). 26 Medical students who…”
Section: Discussionmentioning
confidence: 94%
“…6 Study has shown that this kind of service learning process builds and refines someone's team based skills; improve mental maturity of the students to resolve obstacles etc. 12 Positive feedback by the students has opened the door for similar kind of service and learning activity for future. Model of community service and learning should be encouraged more among the MBBS students by celebrating different national health days in the community and in these activity different models of health education [e.g.…”
Section: Discussionmentioning
confidence: 99%